Whether mindfulness-guided therapy can be a new direction for the rehabilitation of patients with Parkinson’s disease: a network meta-analysis of non-pharmacological alternative motor-/sensory-based interventions - He, Shenglan; Fang, Wanyi; Wu, Jiaoyang; Lv, Hang; Zhang, Jueyu; Wang, Tunyi; Huang, Yingjie; Li, Guangyao; Li, Min (Frontiers in Psychology, 2023)
Background: The treatment of patients withfor Parkinson 's's disease (PD) consumes a lot of manpower and financial resources. non-pharmacological alternative motor/sensory-based interventions is a better choiceare optimized for the rehabilitation of PD patients with Parkinson' s disease.. Mindfulness-guidedbased therapy[1] shows ideal efficacy, but the diversity of the therapy brings difficulties to clinicians' and patients'patients' selection. Methods: Network meta-analysis based onin the Bayesian framework was used to evaluate the efficacy of non-pharmacological alternative motor/sensory-based interventions in improving motor and non-motor symptoms in Parkinson 'sPD patients. Results: A total of 58 studies (22272,227 patients) were included. Compared with the no non-intervention group, qigong was associated with improvement in improved outcomes onin the Timed Up and Go (TUG) test (mean difference (MD =) -5.54, 95% confidence interval (CI [(-) -8.28, to -2.77)])) and [2]UPDRS-I (MD = -15.50, 95% CI [(–19.93, to -7.63)]).). Differences between non-pharmacological alternative motor/sensory-based interventions were not significant for PDQ-39, UPDRS-I, or UPDRS-II,; however, qigong was better thansuperior to dance in TUG (MD = − -3.91, 95% CI [(− -6.90, − to -0.95)]),), taichi (MD = − -3.54, 95% CI [(− -6.53, − to -0.69)]),), acupuncture (MD = − -6.75, 95% CI [(− -10.86, − to -2.70)]),), music (MD = − -3.91, 95% CI [(− -7.49, − to -0.48)])) and exercise groups (MD = − -3.91, 95% CI [(− -6.49, − to -1.33)]).) in the TUG test. Conclusions: This network meta-analysis supports mindfulness-guidedbased therapy (e.g,., qigong, yoga, taichi) as a preferred non-pharmacological alternative motor/sensory-based interventionsintervention for thePD rehabilitation of Parkinson 's patients.